An Extended Model of Sustainable Development from Sustainable Sourcing to Sustainable Reverse Logistics: A Supply Chain Perspective - Hassan Barau Singhry (International Journal of Supply Chain Management, 2015)
Supply chain management is a holistic corporate strategy which involves decisions concerning sourcing, manufacturing, transporting, consumption, and reverse logistics. Although these processes influence competitive advantage, supply chain and organizational performance, they can however, cause sustainability issues if not management holistically. These supply chain processes also put serious burden on the environment with theatrical economic and social costs. The pressures manifest in form of depletion of the natural resources, endangered environment, negative societal norms, and unemployment. However, literature fail to capture the whole process of sustainable supply chain. A break down in one process will affect the performance of others and thus the whole sustainability issue. This study is a literature review where data was taken from previous literature. The finding of this study is an extension of the popular supply chain sustainability framework. It is shown that stakeholder pressure and the pillars of supply chain management such as sustainable practices include sustainable sourcing, sustainable design, sustainable production, sustainable packaging, sustainable transportation, sustainable consumption, and sustainable reverse logistics could be used to improve the theory of sustainable supply chain management. The study concludes with contributions to theory and practice.